Stronger Member States for a Stronger European Union - Mercz, Mónika (Central European Academy Law Review, 2025)
When discussing topics such as national sovereignty and the primacy of European Union (EU) law, the main question boils down to the distribution of competences. We must acknowledge both the historical context of the EU and the current trends in its role in the world’s geopolitical structure. This study focuses on identifying the extent of the limitations surrounding the EU’s power in the Hungarian legislature, how sovereignty is defined, and what aspects of constitutional identity are raised in conversations around this issue. Furthermore, the study aims to present relevant national case law related to the principle of the primacy of EU law and its relationship with Hungary’s national sovereignty and compare it with the position of other Member States’ national courts. This is a vital part of the discussion at hand, which will hopefully lead to an open conversation regarding the future of the EU, the possible outcome of a Convent, and what the continent will look like in the future. The study hypothesises that Member States will follow the trend of attempting to maintain as much sovereignty as possible via the decisions of their Constitutional Courts, in addition to contradicting some EU measures and resisting certain aspirations. Despite this phenomenon, integration is undoubtedly necessary; therefore, this conflict requires an urgent resolution, which will hopefully draw a line in the sand and ensure that the EU can continue, with stronger Member States working together towards a common goal.